Mass Transport Characteristics of Cathodes in a Phosphoric Acid Polybenzimidazole Membrane Fuel Cell - Mamlouk, M.; Scott, K.
A study of the effect of electrode parameters on the mass transport characteristics of cathodes used for oxygen reduction in a phosphoric acid loaded polybenzimidazole membrane fuel cell is reported. Mass transport characteristics were determined using chronoamperometry to measure the dynamic response of electrodes. Mass transfer behavior was analyzed using equations for diffusion in finite lengths of thin film electrolytes covering the catalyst surface area. Electrode structure parameters were measured using SEM images of the cross section of the membrane electrode assemblies. Electrode mass transfer parameters were determined for cathodes using different catalyst Pt loadings and using cathodes which were heat treated to modify micro-structure and hydrophobicity. Analysis of data showed that the dynamic current response was not controlled simply by mass transport by diffusion of oxygen through an electrolyte film covering the catalysts surface, but by an interfacial mass transport at the gas (vapor)/electrolyte film interface. Electrodes which exhibited the better oxygen mass transfer and solubility characteristics also produced better cell voltage versus current density performance in fuel cell studies.
Keywords: PHOSPHORIC ACID; POLYBENZIMIDAZOLE; PBI; FUEL CELL; ELECTRODE PERFORMANCE; MASS TRANSPORT; ELECTRODE STRUCTURE